Struggling with a Gastric Volvulus Secondary to a Type IV Hiatal Hernia - Dafnomilis George; Pappas V. Apostolos; Panoutsopoulos Athanasios; Lagoudianakis E. Emmanuel; Koronakis E. Nikolaos; Panagiotopoulos Nikolaos; Seretis Charalampos; Karanikas George; Manouras J. Andreas (Case Reports in Medicine)
Type IV hiatal hernias are characterized by herniation of the stomach along with associated viscera such as the spleen, colon, small bowel, and pancreas through the esophageal hiatus. They are relatively rare, representing only about 5%–7% of all hernias, and can be associated with severe complications. We report a 71-year-old veteran wrestler who presented to our department with a type IV paraesophageal hernia containing a gastric volvulus and treated successfully with emergency operation.